Kinetics and Mechanism of the Reduction of mer‐Tris‐picolinatoruthenium(III) by L‐Ascorbic Acid. Issue 15 (17th April 2014) - Katafias, Anna; Impert, Olga; Kita, Przemysław; Fenska, Joanna; Koter, Stanisław; Kaczmarek‐Kędziera, Anna; Różycki, Henryk; Bajek, Anna; Uzarska, Małgorzata; van Eldik, Rudi
Abstract: The kinetics of reduction of the mer ‐[Ru III (pic)3 ] complex (pic – = picolinato) by ascorbic acid (AscH2 ) leading to formation of a red ruthenium(II) species have been studied spectrophotometrically by using both conventional mixing and stopped‐flow methods. The reaction was followed as a function of the reductant concentration over a wide pH range (1.0–7.4). Electron transfer proceeds by an outer‐sphere mechanism involving three protolytic forms of ascorbic acid, AscH2, AscH – and Asc 2–, for which specific rate constants have been determined. The Gibbs' energy of activation was found to correlate linearly with the HOMO energies of the protolytic forms of the reductant. The mer ‐[Ru III (pic)3 ] complex is too sparingly soluble in water to inhibit the growth of the Escherichia coli (ATCC 8739) strain. Its cytotoxicity against non‐tumorigenic cells precludes its potential use as an anticancer agent. Abstract : The reduction of mer ‐tris‐picolinatoruthenium(III) byL ‐ascorbic acid as a function of pH can only be studied under well‐selected reaction conditions to prevent the back‐oxidation of tris‐picolinatoruthenium(II) caused by traces of dioxygen. Under such conditions, the redox activity ofL ‐ascorbic acid (AscH2 ) follows the sequence AscH2  << AscH –  << Asc 2– .